Garbhagriha of the Shiva Temple 1 - Temples of India Project Team (Jio Institute, 2024)
The garbhagriha (sanctum sanctorum) of Shiva Temple 1 is a square dark chamber that houses a Shiva linga (aniconic representation of Shiva) with four sides showing four standing deities. The deities on all four sides are shown standing, holding their respective attributes.